Território, paisagem, sujeitos sociais e políticas públicas: (des)caminhos e perspectivas do TBC em comunidades brasileiras e mexicanas - Gomes, Roseane Cristina Santos (2014)
Latin America has as one of its features the landscape diversity that shapes the territory of small communities, these are located in the coastal zone or inside. We refer to the Brazilian and Mexican communities that besides presenting a dynamic landscape have richness sociocultural that singularize them. They possess a richness that sociocultural singularize. They are marked by the traditional lifestyle and the bonds of everyday life. Many of these communities aspire to a better quality of life and seek to excel the exclusion processes which are exposed. Therefore they seek in the tourism, complementing their source of income, or even focus on this activity to maintain their survival. This is the case of the communities studied: villages Crasto/ Santa Luzia do Itanhy, Terra Caída/ Indiaroba Sergipe/ Brazil; Prainha do Canto Verde/Beberibe/Ceará/Brazil e Puerto Morelos/ Benito Juarez county/ Quintana Roo e San Pedro Atlapulco/ Ocoyacac county/ Mexico State México. Feeling the need to reflect on tourism, especially community-based and their impacts on communities cited in geographical science seek the pillar for this reflection. It is envisioned as a factor of socio-spatial transformation, cultural, political and economic. However, for the implementation of this activity, it is relevant to think in host communities, as well and necessity that the territory of social subjects have to receive the tourism. We aim to analyze the socio-spatial relations involving local social subjects, policies to promote tourism and community-based tourism - TBC in Latin American communities already mentioned. It is therefore the analysis of territoriality about that (re) create, (re) signification of the landscape by local social subjects, through the insertion of TBC whose essence the principle of self-management, empowerment of communities and appreciation of the traditional lifestyle. Therefore, we base in the territory and landscape categories to guide the best reflection proposal. We understand that is in the territory where the interaction occurs individual - environment. The method of analysis that substantiates the research is phenomenological. Already the research instruments that were used: literature review; fieldwork consisting of direct observation, survey and photographic record; semi-structured interview technique. Based on the results obtained from the research say that the process of integration of tourism in the communities above mentioned there are several forces acting in the territories of local social subjects. These forces are materialized through the power relations emanating from both communities as agents of the planners of policies encouraging tourism. In the case of political power manifests itself by discourse propagated on local development to achieve sustainability. This really is just a way of alienating maintain control over communities and favor the demands of mass tourism and private actors interested in obtaining foreign currency to invest in tourism. With regard to communities the power comes from the need to defend their territory against external forces which do nothing or very little to contribute to the maintenance of their territoriality. Emanate likewise, the deletion process by which they are submitted, and therefore the search for improvement of their living conditions.